Formaldehyde-free water-based curable composition
By introducing a polymerization of titanium catalyst and a specific monomer ratio into the binder of textiles and nonwovens, a formaldehyde-free aqueous curable composition is formed, which solves the problem of formaldehyde release during heating of traditional binders, and achieves excellent Water resistance and solvent resistance.
Patent Information
- Application Number
- CN202080101942.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-06-19
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2040-06-19
AI Technical Summary
Existing binders for textiles and nonwovens release formaldehyde when heated, resulting in a lack of excellent water and solvent resistance after curing, which is difficult to replace.
The titanium catalyst is introduced into the acrylate binder system to accelerate the curing process and polymerize the monomer mixture in a specific proportion to form a formaldehyde-free aqueous curable composition, including C1-C10 acrylate, vinyl aromatic compounds, with Ethylene unsaturated compounds of carboxylic acid groups and titanium catalysts.
The formaldehyde-free aqueous curable composition has excellent water resistance and solvent resistance after curing, avoiding formaldehyde release, and meeting the replacement needs of traditional binder performance.
Smart Images

Figure GDA0005026246030000091 
Figure GDA0005026246030000101 
Figure GDA0005026246030000121
Abstract
Description
Technical Field
[0001] The present disclosure relates to formaldehyde-free waterborne curable compositions, particularly for paper, textiles, and nonwovens, and also to articles comprising a substrate and the formaldehyde-free waterborne curable composition. Background Art
[0002] Conventional binders for textile and nonwoven applications contain N-methylolacrylamide (NMA) as a functional monomer, which imparts excellent water resistance (wet strength) and solvent resistance (isopropyl alcohol strength) to the binder after curing. However, binders containing NMA release formaldehyde when heated. Formaldehyde-free binder products with excellent water resistance (wet strength) and solvent resistance (isopropyl alcohol strength) after curing are desired.
[0003] Therefore, there is a strong need in the art for alternative formaldehyde-free waterborne curable compositions having desirable properties after curing, such as excellent water resistance (wet strength) and solvent resistance (isopropyl alcohol strength). Summary of the invention
[0004] The present disclosure provides formaldehyde-free waterborne curable compositions having desirable properties after curing, such as excellent water resistance (wet strength) and solvent resistance (isopropyl alcohol strength, IPA strength).
[0005] The present inventors have found that introducing a titanium catalyst widely used in polyester synthesis into an acrylate binder system can accelerate the curing process and bring about excellent performance.
[0006] In a first aspect, the present disclosure provides a formaldehyde-free waterborne curable composition, the formaldehyde-free waterborne curable composition comprising:
[0007] A) A polymer obtained by polymerization of a monomer mixture comprising
[0008] (a) 30 to 90% by weight of acrylic acid C1-C 10 Alkyl esters;
[0009] (b) 10 to 60 wt % of a vinyl aromatic compound;
[0010] (c) 0.5 to 10% by weight of an ethylenically unsaturated compound having at least two carboxylic acid groups;
[0011] (d) 0 to 10% by weight of an ethylenically unsaturated acid having one carboxylic acid group;
[0012] (e) 0 to 5 wt % of other ethylenically unsaturated monomers;
[0013] wherein the percentages are based on the total weight of the monomer mixture, and
[0014] B) Titanium catalyst.
[0015] In a second aspect, the present disclosure provides an article comprising a substrate and a formaldehyde-free waterborne curable composition, the formaldehyde-free waterborne curable composition comprising:
[0016] A) A polymer obtained by polymerization of a monomer mixture comprising
[0017] (a) 30 to 90% by weight of acrylic acid C1-C 10 Alkyl esters;
[0018] (b) 10 to 60 wt % of a vinyl aromatic compound;
[0019] (c) 0.5 to 10% by weight of an ethylenically unsaturated compound having at least two carboxylic acid groups;
[0020] (d) 0 to 10% by weight of an ethylenically unsaturated acid having one carboxylic acid group;
[0021] (e) 0 to 5 wt % of other ethylenically unsaturated monomers;
[0022] wherein the percentages are based on the total weight of the monomer mixture, and
[0023] B) Titanium catalyst.
[0024] In a third aspect, the present disclosure provides a method for treating a substrate, the method comprising contacting a formaldehyde-free waterborne curable composition with the substrate, and then drying and curing the formaldehyde-free waterborne curable composition, wherein the formaldehyde-free waterborne curable composition comprises:
[0025] A) A polymer obtained by polymerization of a monomer mixture comprising
[0026] (a) 30 to 90% by weight of acrylic acid C1-C 10 Alkyl esters;
[0027] (b) 10 to 60 wt % of a vinyl aromatic compound;
[0028] (c) 0.5 to 10% by weight of an ethylenically unsaturated compound having at least two carboxylic acid groups;
[0029] (d) 0 to 10% by weight of an ethylenically unsaturated acid having one carboxylic acid group;
[0030] (e) 0 to 5 wt % of other ethylenically unsaturated monomers;
[0031] wherein the percentages are based on the total weight of the monomer mixture, and
[0032] B) Titanium catalyst.
[0033] It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention, as claimed. DETAILED DESCRIPTION
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. In addition, all publications, patent applications, patents, and other references mentioned herein are incorporated by reference.
[0035] As disclosed herein, the term "composition", "formulation" or "mixture" refers to a physical blend of different components, which is obtained by simply mixing the different components by physical means.
[0036] As disclosed herein, the term "glass transition temperature" (T g ) can be measured by various techniques including, for example, differential scanning calorimetry ("DSC") or by calculation using the Fox equation.
[0037] Throughout this document, the word fragment "(meth)acryl" refers to both "methacryl" and "acryl." For example, (meth)acrylic acid refers to both methacrylic acid and acrylic acid, methyl (meth)acrylate refers to both methyl methacrylate and methyl acrylate, and (meth)acrylamide refers to both methacrylamide and acrylamide.
[0038] By "aqueous" composition or dispersion herein is meant particles dispersed in an aqueous medium. By "aqueous medium" herein is meant water and 0% to 30% by weight of one or more water-miscible compounds, such as, for example, alcohols, glycols, glycol ethers, glycol esters, and the like, based on the weight of the medium.
[0039] The present disclosure provides a formaldehyde-free water-based curable binder composition, the formaldehyde-free water-based curable binder composition comprising:
[0040] A) A polymer obtained by polymerization of a monomer mixture comprising
[0041] (a) 30 to 90% by weight of acrylic acid C1-C 10 Alkyl esters;
[0042] (b) 10 to 60 wt % of a vinyl aromatic compound;
[0043] (c) 0.5 to 10% by weight of an ethylenically unsaturated compound having at least two carboxylic acid groups;
[0044] (d) 0 to 10% by weight of an ethylenically unsaturated acid having one carboxylic acid group;
[0045] (e) 0 to 5 wt % of other ethylenically unsaturated monomers;
[0046] wherein the percentages are based on the total weight of the monomer mixture, and
[0047] B) Titanium catalyst.
[0048] Preferably, (meth)acrylic acid C1-C 10 The alkyl ester is a C1-C8 alkyl (meth)acrylate. The C1-C8 alkyl (meth)acrylate may be selected from ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, n-pentyl acrylate, n-pentyl methacrylate, n-hexyl acrylate, n-hexyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, or a mixture of any two or more thereof. More preferably, the C1-C8 alkyl (meth)acrylate is a C1-C8 alkyl ester. 10 The alkyl ester is selected from butyl acrylate, butyl methacrylate or a mixture thereof.
[0049] Preferably, the (meth)acrylic acid C1-C 10 The amount of the alkyl ester (a) may be not less than 30 wt%, not less than 40 wt%, not less than 50 wt%, not less than 55 wt%, not less than 60 wt%, not less than 65 wt%, or not less than 70 wt%, but not more than 90 wt%, preferably not more than 85 wt%, more preferably not more than 80 wt%. More preferably, the (meth)acrylic acid C1-C 10 The amount of the alkyl ester is from 55% to 85% by weight of the monomer mixture, or from 70% to 80% by weight of the monomer mixture.
[0050] The monomeric vinyl aromatic compound (b) may be styrene, α-methylstyrene or a mixture thereof.
[0051] Preferably, the amount of the vinyl aromatic compound (b) in the monomer mixture may be not less than 10 wt %, preferably not less than 12 wt %, more preferably not less than 15 wt %, even more preferably not less than 18 wt %; but not more than 60 wt %, preferably not more than 50 wt %, more preferably not less than 40 wt %, even more preferably not more than 30 wt %, still more preferably not more than 25 wt %, or not more than 20 wt %.
[0052] The ethylenically unsaturated compound (c) having at least two carboxylic acid groups is, for example, maleic acid, itaconic acid, fumaric acid or a mixture of any two or more thereof.
[0053] Itaconic acid is particularly preferred.
[0054] Preferably, the amount of the ethylenically unsaturated compound (c) having at least two carboxylic acid groups in the monomer mixture may be not less than 0.5 wt %, preferably not less than 1 wt %, more preferably not less than 1.5 wt %, even more preferably not less than 2 wt %, but not more than 10 wt %, preferably not more than 8 wt %, more preferably not more than 6 wt %, even more preferably not more than 5 wt %, still more preferably not more than 3 wt %.
[0055] The ethylenically unsaturated acid (d) having one carboxylic acid group may be acrylic acid and / or methacrylic acid. Preferably, the ethylenically unsaturated acid (d) having one carboxylic acid group is acrylic acid.
[0056] The ethylenically unsaturated acid (d) having one carboxylic acid group is an optional component. Preferably, the amount of the ethylenically unsaturated acid (d) having one carboxylic acid group in the monomer mixture may be not less than 0.5 wt%, preferably not less than 1 wt%, more preferably not less than 1.5 wt%, even more preferably not less than 2 wt%, but not more than 10 wt%, preferably not more than 8 wt%, more preferably not more than 6 wt%, even more preferably not more than 5 wt%, still more preferably not more than 3 wt%.
[0057] Other ethylenically unsaturated monomers (e) are optional components and may be of any kind except (a)-(d). Suitable examples include hydroxyl-containing ethylenically unsaturated monomers, (meth)acrylamide, or phosphorus-functional monomers. The hydroxyl-containing ethylenically unsaturated monomer may be HEMA (hydroxyethyl methacrylate). The phosphorus-functional monomer may be a phosphorus-containing (meth)acrylate, such as ethyl (meth)acrylate phosphate, propyl (meth)acrylate phosphate, butyl (meth)acrylate phosphate, their salts, and mixtures thereof; CH2=C(R)-C(O)-O-(R l O) n -P(O)(OH)2, wherein R=H or CH3, R1=alkyl, and n=2-6, such as SIPOMER PAM-100, SIPOMER PAM-200 and SIPOMER PAM-300, all available from Solvay; (meth)acrylic acid phosphoalkoxy esters, such as phosphoethylene glycol (meth)acrylate, phosphodiethylene glycol (meth)acrylate, phosphotriethylene glycol (meth)acrylate, phosphopropylene glycol (meth)acrylate, phosphodipropylene glycol (meth)acrylate, phosphotripropylene glycol (meth)acrylate, their salts and their mixtures.
[0058] The amount of the hydroxyl-containing ethylenically unsaturated monomer in the monomer mixture may be not less than 0.1 wt %, preferably not less than 0.2 wt %, more preferably not less than 0.5 wt %, even more preferably not less than 0.8 wt %, but not more than 5 wt %, preferably not more than 4 wt %, more preferably not more than 3 wt %, even more preferably not more than 2 wt %, still more preferably not more than 1.5 wt %.
[0059] Preferably, the monomer mixture of the present application does not contain vinyl esters of C1-C18 alkanoic acids or α-olefins such as ethylene or propylene.
[0060] In a preferred embodiment, the polymer A) is prepared by emulsion polymerization and is therefore an emulsion polymer.
[0061] In the case of emulsion polymerization, suitable surfactant systems and / or protective colloids, or stabilizers are used.
[0062] Examples of suitable surfactant systems are those known in the art and include anionic, nonionic, cationic or amphoteric emulsifiers and mixtures thereof. Examples of anionic surfactants include, but are not limited to, sulfates of alkyl sulfates, ethoxylated alcohols, aryl sulfonates, phosphates of ethoxylated alcohols, sulfosuccinates, sulfates and sulfonates of ethoxylated alkylphenols, and mixtures thereof. Examples of nonionic surfactants include, but are not limited to, ethoxylated alcohols, ethoxylated alkylphenols and mixtures thereof. Examples of cationic surfactants include, but are not limited to, ethoxylated fatty amines. Based on the total weight of the monomer, the typical weight of the surfactant is 0.1 wt % to 5.0 wt %, and more preferably 0.3 wt % to 5.0 wt %, and most preferably 0.5 wt % to 3.0 wt %. The surfactant is used by conventional methods well known in the art. In one embodiment, the method for preparing the composition includes emulsifying the monomer mixture with a surfactant system before the polymerization reaction.
[0063] Examples of surfactant trade names are A-102, FES 77, Dowfax TM 2A1, 2535 and DS-4.
[0064] Water-soluble initiators for the emulsion polymerization are, for example, ammonium and alkali metal salts of peroxodisulfate, such as sodium peroxodisulfate, sodium persulfate, ammonium persulfate, hydrogen peroxide, or organic peroxides, such as tert-butyl hydroperoxide.
[0065] Also suitable are known reduction-oxidation (redox) initiator systems.
[0066] Redox initiator systems consist of at least one (usually inorganic) reducing agent and one organic or inorganic oxidizing agent.
[0067] The oxidizing component includes, for example, the emulsion polymerization initiators already mentioned above.
[0068] Reducing components include, for example, alkali metal salts of sulfurous acid, such as sodium sulfite, sodium bisulfite; alkali metal salts of disulfurous acid, such as sodium disulfite; bisulfite addition compounds with aliphatic aldehydes and ketones, such as acetone bisulfite; or reducing agents, such as hydroxymethanesulfinic acid and its salts, or ascorbic acid. Redox initiator systems can be used with soluble metal compounds, the metal component of which can exist in multiple valence states.
[0069] Examples of conventional redox initiator systems include ascorbic acid / iron (II) sulfate / sodium peroxodisulfate, tert-butyl hydroperoxide / sodium bisulfite and tert-butyl hydroperoxide / sodium hydroxymethanesulfinate. The individual components, such as the reducing component, can also be mixtures, such as a mixture of hydroxymethanesulfinate sodium salt and sodium bisulfite.
[0070] These compounds are mostly used in the form of aqueous solutions, with lower concentrations depending on the amount of water acceptable in the dispersion and higher concentrations depending on the solubility of the corresponding compound in water. Based on the solution, the concentration is usually 0.1% to 30% by weight, preferably 0.5% to 20% by weight, particularly preferably 1.0% to 10% by weight.
[0071] The amount of initiator is generally 0.1 to 10% by weight, preferably 0.3 to 5% by weight, based on the monomers to be polymerized. Two or more different initiators can also be used in the emulsion polymerization.
[0072] Emulsion polymerization is generally carried out at 30°C to 130°C, preferably 60°C to 95°C. The polymerization medium may consist of water alone or of a mixture of water and a water-miscible liquid such as methanol. Preferably, only water is used. Emulsion polymerization may be carried out as an intermittent operation or in the form of a feed method, including a segmented or gradient program. A feed method is preferred, in which a portion of the polymerization mixture is introduced as an initial feed and heated to the polymerization temperature, the polymerization of the initial feed is started, and then the remainder of the polymerization mixture is generally supplied to the polymerization zone through two or more spatially separated feed streams, one or more of which contain monomers in linear or emulsified form, the addition being continuous, staged or carried out under a concentration gradient, and the polymerization is maintained during the addition. In order to, for example, set the particle size more effectively, polymer seeds may also be included in the initial feed of the polymerization.
[0073] The manner in which initiators are added to the polymerization vessel during the free radical aqueous emulsion polymerization is known to the skilled person. They may be included in their entirety in the initial charge to the polymerization vessel, or introduced continuously or in stages at the rate at which they are consumed during the free radical aqueous emulsion polymerization. In each particular case, this will depend on the chemical nature of the initiator system and the polymerization temperature. It is preferred to include a portion in the initial charge and to supply the remainder to the polymerization zone at the rate at which they are consumed.
[0074] In order to remove residual monomers, the initiator is usually also added after the actual emulsion polymerization has ended, ie after a monomer conversion of at least 95%.
[0075] During the feed process, the individual components can be added to the reactor from the top, via the side or from the bottom through the reactor floor.
[0076] In the case of emulsion polymerization, aqueous polymer dispersions are obtained having a solids content of generally 15% to 75% by weight, preferably 40% to 75% by weight.
[0077] The polymers prepared in this way are preferably used in the form of their aqueous dispersions.
[0078] The pH of the polymer dispersion is preferably adjusted to a pH of greater than 4.5, in particular to a pH of between 5 and 9.
[0079] The glass transition temperature of the polymer is preferably from -40 to 70°C, particularly preferably from -30 to 65°C, very particularly preferably from -25 to 60°C or from -25 to 5°C.
[0080] The glass transition temperature can be determined by conventional methods, such as differential thermal analysis or differential scanning calorimetry (see, for example, ASTM 3418 / 82, midpoint temperature).
[0081] Component B) is a titanium catalyst.
[0082] The titanium catalyst has the formula Ti(OR)4, wherein each R is independently selected from an alkyl group having about 1 to about 30 carbon atoms, an alkenyl group having about 2 to about 30 carbon atoms, a cycloalkyl group having about 3 to about 30 carbon atoms, an aralkyl group having about 6 to about 30 carbon atoms, and a combination of two or more thereof. Preferably, R is independently selected from an alkyl group having about 1 to about 12 carbon atoms, an alkenyl group having about 2 to about 12 carbon atoms, a cycloalkyl group having about 3 to about 12 carbon atoms, an aralkyl group having about 6 to about 12 carbon atoms, and a combination of two or more thereof. One or more hydrogen atoms of R are optionally replaced by halogen, -OH, -COOH, -NH2, -CN or -NH(C 1-10 Alkyl) or -N(C 1-10alkyl)2 or optionally interrupted by -C(=O)-, -C(=O)-NH-, phosphoryl, phosphoryloxy, sulfonyl or sulfonyloxy.
[0083] The titanium catalyst can be a complex of Ti and an organic polyacid, wherein the organic acid can be a dicarboxylic acid, a tricarboxylic acid, a tetracarboxylic acid or a mixture thereof. Preferably, the organic acid can be selected from citric acid, tartaric acid, EDTA, malic acid, oxalic acid, glutaric acid, adipic acid, suberic acid, itaconic acid or a mixture thereof.
[0084] An example of component B) may be Tyzor ACtivate 436.
[0085] The amount of titanium catalyst is 0.5 to 10 parts by weight per 100 parts by weight of solid polymer A), in particular 1 to 8 parts by weight, very preferably 1.5 to 5 parts by weight, more preferably 2 to 4 parts by weight per 100 parts by weight of solid polymer A).
[0086] Component B) can be added at any point in the process. In one embodiment, it is added after the emulsion reaction.
[0087] The polymers A) or aqueous dispersions of the polymers can be mixed in a simple manner with component B).
[0088] The aqueous composition may include other additives: thickeners, defoamers, wetting agents, mechanical stabilizers, pigments, fillers, freeze-thaw agents, neutralizers, plasticizers, tackifiers (tackifying resins), adhesion promoters, and combinations thereof. Examples of tackifiers are natural resins, such as rosin and its derivatives formed by disproportionation or isomerization, polymerization, dimerization and / or hydrogenation. They may be present in the form of their salts (having, for example, monovalent or polyvalent counterions (cations)) or preferably in the form of their esterification. The alcohol used for esterification may be monobasic or polybasic. Examples are methanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,2,3-propanethiol and pentaerythritol.
[0089] Also used are hydrocarbon resins such as non-hydrogenated aliphatic C5 resins, hydrogenated aliphatic C5 resins, aromatic modified C5 resins, terpene resins, hydrogenated C9 resins, and combinations thereof.
[0090] Other compounds increasingly used as tackifiers include polyacrylates with low molar weights. These polyacrylates preferably have a weight-average molecular weight MW of less than 30,000. Preferably, the polyacrylate consists of at least 60% by weight, in particular at least 80% by weight, of C1-C8 alkyl (meth)acrylates.
[0091] The preferred tackifier is natural or chemically modified rosin. Rosin is mainly composed of abietic acid or its derivatives.
[0092] The amount of the tackifier by weight is preferably 5 to 100 parts by weight, particularly preferably 10 to 50 parts by weight, based on 100 parts by weight of the polymer (solid / solid).
[0093] The curable aqueous composition may include 0 wt % to 5 wt % thickener, based on the total weight of the binder composition. All individual values and subranges from 0 to 5 wt % are included and disclosed herein. For example, the weight % of the neutralizer may be a lower limit of 0 wt %, 0.5 wt %, or 1 wt % to an upper limit of 1 wt %, 3 wt %, or 5 wt %. Exemplary thickeners include, but are not limited to, ACRYSOL TM 、UCAR TM and CELOSIZE TM , which are commercially available from The Dow Chemical Company, Midland, Michigan.
[0094] Based on the gross weight of the binder composition, the curable aqueous composition may include 0 wt % to 2 wt % of a neutralizer. All individual values and subranges of 0 wt % to 2 wt % are included and disclosed herein. For example, the weight % of the neutralizer can be a lower limit of 0,0.3 wt % or 0.5 wt % to an upper limit of 0.5 wt %, 1 wt % or 2 wt %. Neutralizers are generally used to control pH to provide stability to the binder composition of formulation. Examples of neutralizers include, but are not limited to, ammoniacal liquor, aqueous amines and other aqueous inorganic salts.
[0095] The formaldehyde-free waterborne curable composition may be cured at a temperature of 120°C to 200°C, preferably at a temperature of 150°C to 180°C.
[0096] The formaldehyde-free waterborne curable composition can be applied to substrates such as paper, textiles, or nonwovens to form articles.
[0097] To treat the substrate, the substrate can be conventionally coated with the formaldehyde-free aqueous curable composition, such as by dipping, spraying, knife coating, etc. Conventional application rates are, for example, 5 to 50 g / m 2 (Solid, anhydrous).
[0098] The articles of the present invention have good performance properties, particularly high wet strength and / or IPA strength.
[0099] The present disclosure also provides a method for treating a substrate, the method comprising contacting the formaldehyde-free waterborne curable composition as described herein with the substrate, and then drying and curing the formaldehyde-free waterborne curable composition.
[0100] The substrate can be paper, textile or nonwoven.
[0101] Contacting the formaldehyde-free waterborne curable composition as described herein with the substrate can be achieved by immersing the substrate in the formaldehyde-free waterborne curable composition as described herein or spraying the formaldehyde-free waterborne curable composition as described herein on the substrate.
[0102] Example
[0103] Some embodiments of the present invention will now be described in the following examples, in which all parts and percentages are by weight unless otherwise indicated.
[0104] raw materials :
[0105] Table 1: Raw materials
[0106]
[0107]
[0108] *Tyzor ACtivate 436 is a composite of Ti and citric acid, wherein the Ti content is 5 wt%.
[0109] Emulsion Polymerization Procedure
[0110] Acrylic emulsion (A) :
[0111] sample Composition Notes SWX1321(A-I1) 59BA / 35St / 2.5AA / 2.5IA / 1HEMA Sample of the present invention, Tg = 5°C SWX1331(A-I2) 76BA / 18St / 2.5AA / 2.5IA / 1HEMA Sample of the present invention, Tg = -25°C SWX1336(A-I3) 76BA / 19St / 2.5AA / 2.5IA Sample of the present invention, Tg = -25°C
[0112] 1. Synthesis of acrylic emulsion (A)
[0113] SWX1321 containing 59 wt% BA, 35 wt% Sty, 2.5 wt% AA, 2.5 wt% IA, 1 wt% HEMA, based on the dry weight of the copolymer, was prepared according to the following method.
[0114] Preparation of Monomer Emulsion (SWX1321) - 5.77 g RHODACAL DS-4 (DS-4) was dissolved in 475 g deionized water (DI water). An emulsified monomer mixture was prepared by slowly adding the following chemicals to the stirred solution: 6.84 g IA, 13.7 g HEMA, 34.2 g AA, 806.6 g BA, 478.5 g Sty.
[0115] A solution containing 50.42 g of DS4 and 370 g of deionized water (hereinafter referred to as "DI water") was placed in a 5-neck 5-liter round-bottom flask equipped with a thermocouple, a cooling condenser and a stirrer and heated to 70°C under nitrogen. 27.4 g of itaconic acid (IA) in 255 g of 60°C DI water was charged to the flask. Then 82.8 g of the monomer emulsion was charged to the flask. Then 3.72 g of sodium persulfate (SPS) in 25 g of DI water and 1.86 g of sodium bisulfite (SBS) in 20 g of DI water were charged to the flask. When the exothermic peak appeared and the temperature was 70°C, the remaining monomer emulsion, SPS solution (2.48 g in 50 g of DI water) and SBS solution (1.24 g in 50 g of DI water) were fed within 120 minutes. The polymerization temperature was maintained at 69°C to 71°C. After the addition was complete, the container containing the monomer emulsion and the feed tube to the flask were rinsed with 90 g of DI water and the rinse was added back to the flask. The flask was then held at 70° C. for 15 minutes. Thereafter, a solution of t-BHP (70%, 5.03 g in 48 g of DI water) and Bruggolite FF6 (4.28 g in 52 g of DI water) was gradually added over 60 minutes and the reaction was cooled to room temperature. 110 g of 20% sodium hydroxide solution was added to adjust the pH to 6.5-7.5. The solids content was 46%.
[0116] SWX1331 containing 76 wt% BA, 18 wt% Sty, 2.5 wt% AA, 2.5 wt% IA, 1 wt% HEMA, based on the dry weight of the copolymer, was prepared according to the following method.
[0117] Preparation of Monomer Emulsion (SWX1331) - 47.72 g DS-4 was dissolved in 475 g deionized water (DI water). An emulsified monomer mixture was prepared by slowly adding the following chemicals to the stirred solution: 6.84 g IA, 13.7 g HEMA, 34.2 g AA, 1039.1 g BA, 246.1 g Sty.
[0118] A solution containing 8 g of DS4 and 370 g of deionized water (herein referred to as "DI water") was placed in a 5-neck 5-liter round-bottom flask equipped with a thermocouple, a cooling condenser and a stirrer and heated to 70°C under nitrogen. 27.4 g of itaconic acid (IA) in 255 g of 60°C DI water was charged to the flask. Then 82.8 g of the monomer emulsion was charged to the flask. Then 2.48 g of sodium persulfate (SPS) in 25 g of DI water and 1.24 g of sodium bisulfite (SBS) in 20 g of DI water were charged to the flask. When the exothermic peak appeared and the temperature was 70°C, the remaining monomer emulsion, SPS solution (2.48 g in 50 g of DI water) and SBS solution (1.24 g in 50 g of DI water) were fed in 120 minutes. The polymerization temperature was maintained at 69°C to 71°C. After the addition was complete, the container containing the monomer emulsion and the feed tube to the flask were rinsed with 90 g of DI water and the rinse was added back to the flask. The flask was then held at 70° C. for 15 minutes. Thereafter, a solution of t-BHP (70%, 5.03 g in 48 g of DI water) and Bruggolite FF6 (4.28 g in 52 g of DI water) was gradually added over 60 minutes and the reaction was cooled to room temperature. 110 g of 20% sodium hydroxide solution was added to adjust the pH to 6.5-7.5. The solids content was 46%.
[0119] SWX1336 was prepared according to the same process as SWX1331, except for the formulation of the monomer emulsion: 47.72 DS-4 was dissolved in 475 g deionized water (DI water). An emulsified monomer mixture was prepared by slowly adding the following chemicals to the stirred solution: 6.84 g IA, 34.2 g AA, 1039.1 g butyl acrylate, 259.8 g styrene.
[0120] 2. Dry / Wet / IPA tensile strength test
[0121] The above raw materials were formulated under appropriate stirring for 15 minutes to obtain a curable aqueous composition according to the formulation in Table 2.
[0122] A 28cm×46cm WHATMANTM paper was immersed in 300mL of the prepared emulsion. The treated substrate was stretched using a Mathis stretching machine and then dried and cured at 150°C for 3 minutes. The amount of polymer added to the paper was controlled between 14% and 16%. The cured substrate was cut into 1 inch×4 inch pieces, where the 4-inch direction was the transverse (CD) direction of the paper. The tensile strength of the samples was tested on an Instron under dry (untreated), wet (after immersion in 0.1% Triton X-100 / water solution for 30 minutes) and IPA (after immersion in isopropyl alcohol for 30 minutes). Wet strength reflects the adhesive's resistance to water, while IPA strength reflects the adhesive's resistance to solvents.
[0123] The water resistance of the saturated cellulose substrate was evaluated. The data are shown in Table 3.
[0124] Table 2: Sample formulations .
[0125]
[0126] *The values in brackets () are the solid ratios in the formula
[0127] Table 3: Application test of samples .
[0128]
[0129]
[0130] *Δ represents the wet / IPA strength improvement with B component in the formulation.
[0131] Higher strength values represent better performance. The results in Table 3 show that all examples do not contain HCHO. Compared with Comparative Examples 1 to 3, Examples 1 to 6 of the present invention having component B in the formulation show 9% to 40% improvement in wet strength and 10% to 40% improvement in IPA strength.
[0132] This improvement is believed to come from the catalytic effect of the titanium on the reaction between the carboxyl groups in the formulation and the hydroxyl groups on the textile and nonwoven substrates.
Claims
1. A formaldehyde-free waterborne curable composition, comprising: A) a polymer obtained by polymerization of a monomer mixture, wherein the monomer mixture comprises (a) 30 to 90% by weight of acrylic acid C1-C 10 Alkyl esters; (b) 10 to 60 wt % of a vinyl aromatic compound; (c) 0.5 to 10% by weight of an ethylenically unsaturated compound having at least two carboxylic acid groups; (d) 0 to 10% by weight of an ethylenically unsaturated acid having one carboxylic acid group; (e) 0 to 5 wt % of other ethylenically unsaturated monomers, wherein the other ethylenically unsaturated monomers are selected from hydroxyl-containing ethylenically unsaturated monomers, (meth)acrylamide or phosphorus-functional monomers; wherein the percentages are based on the total weight of the monomer mixture, and the sum of the weight percentages of components (a), (b), (c), (d) and (e) equals 100%; as well as B) Titanium catalyst.
2. The water-based curable composition according to claim 1, wherein the acrylic acid C1-C 10 The amount of alkyl ester is from 55% to 85% by weight.
3. The water-based curable composition according to claim 1, wherein the acrylic acid C1-C 10 The alkyl ester is selected from ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, n-pentyl acrylate, n-pentyl methacrylate, n-hexyl acrylate, n-hexyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate or a mixture of any two or more thereof.
4. The waterborne curable composition according to claim 1, wherein the vinyl aromatic compound is selected from styrene, α-methylstyrene or a mixture thereof.
5. The waterborne curable composition according to claim 1, wherein the amount of the vinyl aromatic compound in the monomer mixture is 15 to 35 wt%.
6. The waterborne curable composition according to claim 1, wherein the ethylenically unsaturated compound having at least two carboxylic acid groups is selected from maleic acid, itaconic acid, fumaric acid or a mixture of any two or more thereof.
7. The waterborne curable composition according to claim 1, wherein the ethylenically unsaturated acid having one carboxylic acid group is selected from acrylic acid, methacrylic acid or a mixture thereof.
8. The waterborne curable composition according to claim 1, wherein the amount of the titanium catalyst is 0.5 to 10 parts by weight per 100 parts by weight of the solid of the polymer A).
9. The aqueous curable composition according to claim 1, wherein the titanium catalyst has the formula Ti(OR)4, wherein each R is independently selected from an alkyl group having 1 to 30 carbon atoms, an alkenyl group having 2 to 30 carbon atoms, a cycloalkyl group having 3 to 30 carbon atoms, an aralkyl group having 6 to 30 carbon atoms, and a combination of two or more thereof, wherein one or more hydrogen atoms of R are optionally replaced by halogen, -OH, -COOH, -NH2, -CN or -NH(C 1-10 Alkyl) or -N(C 1-10 alkyl)2 or optionally interrupted by -C(=O)-, -C(=O)-NH-, phosphoryl, phosphoryloxy, sulfonyl or sulfonyloxy; Alternatively, the titanium catalyst is a composite of Ti and an organic polyacid.
10. The waterborne curable composition of claim 1, wherein the polymer has a glass transition temperature of -40°C to 70°C.
11. An article comprising a substrate and the formaldehyde-free waterborne curable composition according to any one of claims 1 to 10.
12. The article of claim 11, wherein the substrate is a textile or a nonwoven.
13. The article of claim 11, wherein the substrate is paper.
14. A method for treating a textile or nonwoven fabric, the method comprising contacting the formaldehyde-free waterborne curable composition according to any one of claims 1 to 10 with a substrate, and then drying and curing the formaldehyde-free waterborne curable composition.